O MEMORIAL DO OUTRO: A DINÂMICA DE SOBREVIVÊNCIA PELA ESCRITA NA OBRA OS ANOS, DE ANNIE ERNAUX - Siqueira, Maria Elisa Barbosa (Revista (Entre Parênteses), 2025)
The present article investigates the writing project in The Years (2021) by Annie Ernaux, in which her private experience is used as a tool to recount collective history in France. The act of writing her memories reveals a principle of provocation and questioning about the social context of the time. Photographs, elements reconstructed through the materiality of the text, reveal the outline of an undefined being, the portrait of a biographical subject that does not rely on the grammatical category of “I”. The observation that only the pronouns “we” and “she” are used underscores how readers of the work are engaged through referential games, in which the intrusion of the other allows history lost in the past to be preserved for the future. For this analysis, the concepts developed by Leonor Arfuch, Roland Barthes, Pedro G. D. Brito, Serge Doubrovsky, Philippe Dubois, Gabriela S. Freitas, and Jovita M. G. Noronha will be employed. Ernaux's work is a memorial to society, a space of which she is a part and where she becomes the narrator of the multiple perspectives that surround her.